Perencanaan Ekowisata Berbasis Sarana dan Prasarana - Andi Iswahyudi Raden M. P.; Slamet Trisutomo; Muhammad Fathien Azmy (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2018)
Majene Regency is located in West Sulawesi Province, which is one of the areas with coastal tourism potential, one of which is Dato Beach. Dato Beach has the beauty of a tropical beach that is divided into two parts, namely, sandy beaches and coral reef beach tourism. This study aims to identify potential and problems and formulate direction for ecotourism planning. Data collection methods used are observation and literature study. While the analytical method used is, descriptive analysis of the potential and problems of Dato Beach, scoring analysis, and spatial analysis. The results of this research show the potential of Dato Beach, namely, the potential of tourist attractions such as natural scenery, swimming, fishing, snorkeling, diving, boating and other activities. However, the problems that hamper the development of Dato Beach as a tourist area, namely, the lack of adequate infrastructure such as clean water, public toilets, trash bins and also access roads that are not yet URL. The direction of ecotourism planning for Dato Beach focuses on four components, namely, tourist attractions, zoning, infrastructure, and accessibility.